University of Minho Open Access Experience: OpenAIRE, OpenAIREplus, MedOANet, RCAAP Projects and Institutional Repository Erasmus Staff Mobility Program and Training, July, 23-27, 2012 - Can Besimoğlu (Türk Kütüphaneciliği)
In this study Open Access training impressions at University of Minho are presented. The Erasmus staff mobility program contains OpenAIRE, OpenAIREplus, MedOANet and RCAPP projects. Additionaly, have gotten detailed information about University of Minho Institutional Reporistory (RepositoriUM). With the Erasmus program, experiences gained about important Open Access projects and institutional repository.